PELAPORAN AUDIT KEPATUHAN DANA KAMPANYE PADA PARTAI X KOTA P TERHADAP TRANSPARANSI DAN AKUNTABILITAS - Davin Windiarta; Hero Priono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Campaigning is an important stage in an election, where parliamentary candidates present their vision and mission. The success of the campaign is highly dependent on the availability of adequate funding. Elections must be conducted in a fair and transparent manner, including in terms of political party finances PKPU No.18 of 2023 and KPU No. 1677 regulate campaign funds to prevent fraud and increase transparency. The results of the 2024 election campaign fund audit showed non-compliance by Party X Kota P with the rules. These findings are important for evaluating Party X's integrity in campaign fund management, which in turn will increase public trust in the electoral process. This research uses qualitative methods to analyze political party financial report data, focusing on transparency and accountability. The findings show that party X Kota P still does not understand the regulations applied by the General Election Commission.